Urban Conservation in International Charters: From the Athens Charter to the Historic Urban Landscape Recommendation - Frenda, Antonino; Valle, Marco (Protection of Cultural Heritage, 2021)
The Interreg CE project “RUINS. Sustainable re-use, preservation and modern management of historical ruins in Central Europe - elaboration of integrated model and guidelines based on the synthesis of the best European experiences” has implemented cultural development strategies through knowledges exchange developed within a local and regional context and suitable to be applied at a wider European level. The project has applied an empowering bottom-up approach, in which local and regional stakeholders have been actively engaged throughout the project’s running time. Cooperation of 6 countries with various traditions and experiences resulted in the development of universal models that could be applied for management, use and protection of medieval ruins all over Europe, providing European added value. The comprehensive management plans elaborated, help owners and managers of historical ruins to exploit economic potential of this heritage in economic development of regions, and to preserve value of medieval ruins as cultural heritage. Due to the transnational character, the project has contributed to create a common European identity, strengthen cooperation between international, national and local stakeholders both vertically and horizontally, and promote exchanges between boundaries. The paper aims to present the results and the experience gained during RUINS project implementation by LINKS Foundation (project partner), focusing on the inclusive and shared approaches carried out. A summary of goals and recommendations achieved within the discussion panels/seminars arranged by LINKS Foundation as well as objectives and structure of the Output O.T2.1 “BEST PRACTICES HANDBOOK - Transnational model form of socially useful use of medieval ruins" will be provide.